Peran Literasi Digital Membentuk Sikap Kewarganegaraan Mahasiswa terhadap Disinformasi, Informasi Viral dan Flexing Media Sosial - Arkan Bintang Gunawan; Zahra Nur Istiqamah; Syfa Amelia Putri; Cindi Imelia Silaban (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The rapid development of social media has changed the way students obtain, process, and disseminate information in their daily lives. These changes present various challenges, including the spread of misinformation, the increase in viral content, and the emergence of a culture of showing off, which can influence students' attitudes and behavior in the digital age. This study aims to analyze the role of digital literacy in shaping students' civic attitudes in addressing these phenomena. This study employed a descriptive qualitative approach, collecting data through interviews, observations, and documentation conducted with students who actively use social media. The results indicate that digital literacy skills play a role in enhancing students' critical thinking skills in evaluating information, verifying facts, and using social media more responsibly. Students with strong digital literacy skills tend to be more resistant to fake news, unverified information, or exaggerated lifestyles displayed on social media. Consequently, improving digital literacy is a crucial factor in developing responsible students with critical thinking skills who are able to contribute to a positive and healthy digital environment.